Content, Convenience and Community: The Keys to Adult Jewish Learning During the COVID-19 Pandemic. Issue 1 (2nd January 2022) - Schwartz, Morey
ABSTRACT: A survey of online adult Jewish learning during the COVID-19 pandemic has revealed some key elements that have drawn learners aged 65–75 to continued online study. These key elements may play a role in future learner choices and, therefore, might be considered by adult Jewish learning providers in the post-pandemic period. The shift to online learning during the pandemic not only served as a prominent substitute method for the delivery of adult Jewish learning, for many of these learners it also expanded their interest in adult Jewish learning and offered them a significantly more convenient alternative for accessing it. Perhaps most interesting and most significant is the extent to which regular ongoing learning as part of an online cohort of adult learners is offering participants an unexpected, genuine sense of community, something that adult Jewish learners consider to be central to a successful learning experience.